2017
DOI: 10.31234/osf.io/ek3u7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent roles of autistic and alexithymic traits in utilitarian moral judgments in adults with autism

Abstract: This study investigated hypothetical moral choices in adults with high-functioning autism and the role of empathy and alexithymia in such choices. We used a highly emotionally salient moral dilemma task to investigate autistics' hypothetical moral evaluations about personally carrying out harmful utilitarian behaviours aimed at maximizing welfare. Results showed that they exhibited a normal pattern of moral judgments despite the deficits in social cognition and emotional processing. Further analyses revealed t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 67 publications
4
30
4
Order By: Relevance
“…In contrast to original study, it was found that impartial beneficence was positively correlated with psychopathy while instrumental harm negatively correlated with psychopathy. As mentioned before generally psychopathy was found to be positively and empathy was found to be correlated negatively with utilitarianism in the literature (Bartels & Pizarro, 2011;Carmona-Perera, Verdejo-García, Young, Molina-Fernandez, & Pérez-García, 2012;Duke & Bègue 2014;Gleichgerrcht & Young, 2013;Kahane et al, 2015;Gleichgerrcht & Young, 2013;Kahane, Everett, Earp, Farias, & Savulescu, 2015;Koenigs, Kruepke, Zeier, & Newman, 2012;Patil, Melsbach, Hennig-Fast & Silani, 2016). In their scale validation study Kahane et al (2017) aimed to differentiate utilitarianism in two dimensions.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to original study, it was found that impartial beneficence was positively correlated with psychopathy while instrumental harm negatively correlated with psychopathy. As mentioned before generally psychopathy was found to be positively and empathy was found to be correlated negatively with utilitarianism in the literature (Bartels & Pizarro, 2011;Carmona-Perera, Verdejo-García, Young, Molina-Fernandez, & Pérez-García, 2012;Duke & Bègue 2014;Gleichgerrcht & Young, 2013;Kahane et al, 2015;Gleichgerrcht & Young, 2013;Kahane, Everett, Earp, Farias, & Savulescu, 2015;Koenigs, Kruepke, Zeier, & Newman, 2012;Patil, Melsbach, Hennig-Fast & Silani, 2016). In their scale validation study Kahane et al (2017) aimed to differentiate utilitarianism in two dimensions.…”
Section: Discussionmentioning
confidence: 93%
“…Gleichgerrcht and colleagues (2013) found that when asked how strongly they felt about their decisions, autistic adults reported greater emotional arousal following trolley decisions and less emotional arousal following footbridge decisions compared with neurotypical participants. Patil and colleagues (2016) asked participants how emotionally arousing they found the scenarios (not their decisions) and found that autistic adults reported more emotional arousal than neurotypical participants regardless of the dilemma type. Patil and colleagues (2016) added a measure of alexithymia and conducted a path analysis of the autistic participants’ data to further investigate responses to the footbridge dilemma.…”
Section: Resultsmentioning
confidence: 99%
“…Representing internal states of others requires an understanding of those states as distinct from one's own, i.e., theory of mind, or mentalizing (Wimmer & Perner, 1983). Despite autistic individuals' ability to attribute mental states to others during theory of mind tasks (Baron-Cohen, Leslie, & Frith, 1985), mentalizing has been found to be less automatic among this population, suggesting a compensatory cognitive strategy for mentalizing (e.g., verbal reasoning skills: Senju, Southgate, White, & Frith, 2009; or nonverbal reasoning skills: Patil, Melsbach, Hennig-Fast, & Silani, 2016). Development and execution of rationalist moral judgement therefore requires psychological processes and cognitive skills that could be atypical among autistic individuals.…”
Section: Rationalist Moral Developmentmentioning
confidence: 93%
See 2 more Smart Citations